Comparison of Influenza and Coronavirus Disease 2019–Associated Hospitalizations Among Children Younger Than 18 Years Old in the United States: FluSurv-NET (October–April 2017–2021) and COVID-NET (October 2020–September 2021). (20th May 2022) - Delahoy, Miranda J; Ujamaa, Dawud; Taylor, Christopher A; Cummings, Charisse; Anglin, Onika; Holstein, Rachel; Milucky, Jennifer; O'Halloran, Alissa; Patel, Kadam; Pham, Huong; Whitaker, Michael; Reingold, Arthur; et al.
Abstract: Background: Influenza virus and SARS-CoV-2 are significant causes of respiratory illness in children. Methods: Influenza- and COVID-19–associated hospitalizations among children <18 years old were analyzed from FluSurv-NET and COVID-NET, 2 population-based surveillance systems with similar catchment areas and methodology. The annual COVID-19–associated hospitalization rate per 100 000 during the ongoing COVID-19 pandemic (1 October 2020–30 September 2021) was compared with influenza-associated hospitalization rates during the 2017–2018 through 2019–2020 influenza seasons. In-hospital outcomes, including intensive care unit (ICU) admission and death, were compared. Results: Among children <18 years, the COVID-19–associated hospitalization rate (48.2) was higher than influenza-associated hospitalization rates: 2017–2018 (33.5), 2018–2019 (33.8), and 2019–2020 (41.7). The COVID-19–associated hospitalization rate was higher among adolescents 12–17 years old (COVID-19: 59.9; influenza range: 12.2–14.1), but similar or lower among children 5–11 (COVID-19: 25.0; influenza range: 24.3–31.7) and 0–4 (COVID-19: 66.8; influenza range: 70.9–91.5) years old. Among children <18 years, a higher proportion with COVID-19 required ICU admission compared with influenza (26.4% vs 21.6%; P < .01). Pediatric deaths were uncommon during both COVID-19– and influenza-associated hospitalizations (0.7% vs 0.5%; P = .28). Conclusions: In the setting of extensive mitigation measures during the COVID-19 pandemic, the annual COVID-19–associated hospitalization rate during 2020–2021 was higher among adolescents and similar or lower among children <12 years compared with influenza during the 3 seasons before the COVID-19 pandemic. COVID-19 adds substantially to the existing burden of pediatric hospitalizations and severe outcomes caused by influenza and other respiratory viruses. Abstract : Annual hospitalization rates and proportions of hospitalized children experiencing severe outcomes were as high or higher for COVID-19 during October 2020–September 2021 compared with influenza during the 3 seasons before the COVID-19 pandemic, based on US population–based surveillance data.